Patofisiologi dan Diagnosis Penurunan Kesadaran pada Penderita Diabetes Mellitus - Ian Huang (Fakultas Kedokteran Universitas Pelita Harapan, 2018)
Loss of consciousness (LOC) is a clinical presentation of patients with diabetes mellitus (DM) in emergency department which is caused by complications of the disease. Diabetic ketoacidosis, hyperosmolar hyperglycemic state, lactic acidosis, uremic encephalopathy, and hypoglycemia are the several main causes of LOC in patients with DM. The comprehension of pathophysiology of LOC in patients with DM will be helpful in making accurate diagnosis. History taking, physical examination, and laboratory tests are essential in diagnosing that particular condition. Key Words: loss of consciousness, diabetes mellitus, hyperglycemic crisis, hypoglycemia